Implications of Forest Policy Changes on Investment Program Strengthening Forest Management Unit in Central Sulawesi - Sudirman Daeng Massiri (Department of Forestry, Faculty of Agriculture, University of Lampung, 2023)
The forest investment program, supported by foreign funding, aims to promote the strengthening of Forest Management Units (FMUs) in implementing decentralized forest management in Indonesia. Ten FMUs have received funding from the forest investment program since 2017, one of which is FMU Dampelas Tinombo of Central Sulawesi. This program exited in 2022. During its implementation project, Indonesia’s forestry policy is changing, as are the primary tasks and functions of FMUs. This study examined the implication of forest policy changes on the sustainability of the FMU strengthening investment program in FMU Dampelas Tinombo of Central Sulawesi Province. This study was conducted from July to September 2022. Data was collected through interviews and focused group discussions with FMU managers and stakeholders. This study showed that the forest investment program to strengthen the FMU in Central Sulawesi had been effectively implemented but had not significantly affected decentralized forest management practices. Changes in forestry policy brought about by the amendment of the Job Creation Law and its subsidiary regulations have significantly affected the program’s performance and sustainability. The business development program promoting FMU independence must be discontinued because it contradicted the FMUS’ constitutionally mandated primary responsibilities and duties. FMU should optimize the governance function in achieving community-based forest management, which includes forest planning, facilitation, and technical guidance. Keywords: Forest management unit, forest policy change, governance, performance, sustainability